Mekanisme Penanganan Customer service terhadap Complaint Nasabah (Studi Kasus pada Bank Sumatera Utara Cabang Syariah): Customer service Handling Mechanism for Customer Complaints (Case Study at North Sumatra Bank Sharia Branch) - Akbar, Sandy; Wini Istya Sari (Experimental Student Experiences, 2022)
In the current economy, the relationship between banks and the community is very difficult to separate because banks also really need funds from the community, which is one of their main sources. The purpose of this study is to find out the mechanism for handling customer service for customer complaints at the sharia branch of North Sumatra banks. This study uses a qualitative method with a descriptive approach. Data collection techniques through the results of observations made at the North Sumatra Sharia Bank Branch. Based on the experience of several employees of Bank Sumut KC Medan Syariah customers who have received claims related to failed transactions, handling them is much better done by completing claims within the specified time period or even before the specified time period. expired. In addition, customers who use reliable customer service can improve their financial situation. Based on the experience of several employees of Bank Sumut KC Medan Syariah customers who have received claims related to failed transactions, handling them is much better done by completing claims within the specified time period or even before the specified time period. expired. In addition, customers who use reliable customer service can improve their financial situation.